PENGARUH PELATIHAN, PENGALAMAN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJAPEGAWAI NEGERI SIPIL - ANGGITA ANGGITA; SETIA TJAHYANTI (Jurnal Bisnis dan Akuntansi, 2017)
The purpose of this study was to determine the effect of several variables such as training, work experience and work environment to civil servant performance. The object of this research is the State Asset Service Office and Auction area Jakarta III. The method used is Descriptive and Methods simple regression were used to test the hypothesis. Respondents involved in this study were 51 employees. This study uses a sampling method saturated. Data collection technique of collecting data by using questionnares. The results showed that the partial Training does not affect employee performance, Work experience partially affect the civil servant Performance, work environment partially affect Employee performance.